Assessment of Vitamin D Level in Psoriasis and Psoriatic Arthritis Patients - Obaid Ur Rahman, Aurangzaib Khan, Munaza Khattak, Shabir Ahmed Orakzai, Tehseen Naveed, Mohammad Farooq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Investigating the relationship between vitamin D status and psoriasis and psoriatic arthritis is the goal of this investigation. Methods: 120 individuals with psoriasis & 38 patients with psoriatic arthritis (PsA) participated in a case-control research; 89 (56.3%) of the patients were men. Every patient with psoriasis had their erythrocyte sedimentation rate (ESR) and disease activity score utilizing 28 joints (DAS28) computed, and every person with PsA had their disease area and severity index (PASI) assessed. 164 volunteers, matched for age and sex (91 men and 73 women), made up the control group. Serum vitamin D levels were measured in both patients and controls. Results: Both patients’ and controls’ vitamin D levels were 17.4and 28.3 respectively. When compared to patients with disease durations of 10 years or less, the level of vitamin D was lower in patients with disease durations equal to or greater than that. The two patient groupings’ vitamin D levels do not significantly differ from one another. Psoriasis and PsA have been associated with elevated PASI and DAS28 levels due to low vitamin D levels. Conclusion: Low blood Vitamin D levels are connected with patients who have psoriasis and PsA. In both PsA and psoriasis, vitamin D insufficiency has been linked to the persistence of the illness. Keywords: vitamin, psoriasis, diseases severity index, psoriatic arthritis